Effect of calcium chloride application on mango fruit cv. Tommy Atkins hydrothermally treated - Júnior, Murillo Freire; Chitarra, Adimilson Bosco (Pesquisa Agropecuaria Brasileira, 1999)
The aim of this work was to study the effects of the application of calcium chloride associated with hydrothermal treatment on post-harvest preservation of mango fruit (Mangifera indica L.). The Ca absorption by mango peel and flesh was investigated using the same conditions usually employed for the fruit exportation to the american market. It was verified that the association of heat treatment to Ca application was viable. There was a positive correlation between the amount of Ca applied and the amount of this element presented in the peel, although low penetration toward the flesh was observed. It was demonstrated that Ca reduces anthracnose symptoms. It was also verified, by observing the external appearance of the fruits, that the best results were obtained when 4% of calcium chloride was used, although such concentration did not guarantee the required quality for the fruit exportation. The calcium chloride application was not effective to increase the shelf-life of the fruits.
Keywords: Mangifera indica; post harvest treatment